Day‐to‐day physical functioning and disability in obese 10‐ to 13‐year‐olds. Issue 1 (7th September 2012) - Tsiros, M. D.; Buckley, J. D.; Howe, P. R. C.; Olds, T.; Walkley, J.; Taylor, L.; Mallows, R.; Hills, A. P.; Kagawa, M.; Coates, A. M.
Summary What is already known about this subject? Compared with their healthy‐weight peers, children with obesity have; impaired physical health‐related quality of life reduced physical activity levels reduced capacity to perform certain weight‐bearing tasks in field‐based fitness tests What this study adds? First investigation of obesity‐related disability in children using the International Classification for Functioning, Disability and Health framework for Children and Youth. Obesity in children appears to be associated with disability impacting basic locomotor skills and physical health‐related quality of life. Children's participation in key life areas related to physical functioning appears to be minimally impacted by obesity. Objective The aim of this study was to investigate whether obesity is related to impaired day‐to‐day physical functioning and disability in children. Methods An observational case–control study was conducted in three Australian states. Obese (n = 107) and healthy‐weight (n = 132) 10‐ to 13‐year‐olds (132 male, 107 female) were recruited via media advertisements. Assessment of body composition (dual energy X‐ray absorptiometry), locomotor capacity (six‐minute walk test [6MWT], timed up and down stairs test [TUDS] and timed up and go [TUG]) and child‐reported physical health‐related quality of life (HRQoL) were undertaken. Participants wore an accelerometer for 8 days and completed two use‐of‐time telephone interviews to assess participation in key life areas. Results Compared with their healthy‐weight counterparts, obese children had lower physical HRQoL scores (P < 0.01) and reduced locomotor capacity (TUDS z‐score, TUG and 6MWT; P < 0.01). Higher percent body fat was significantly related to lower physical HRQoL scores (r = −0.48, P < 0.01), slower performance times for the TUDS and TUG (r = 0.59 and 0.26 respectively, P < 0.01), shorter 6MWT distances (r = −0.51, P < 0.01) and reduced time spent in community participation activities (r = −0.23, P < 0.01). Conclusions As anticipated, obesity appears to undermine physical functioning in children, including the capacity to perform basic locomotor skills yet, unexpectedly, participation in key life areas related to physical functioning appeared largely unaffected.